Effectiveness of sustained maximal inspiration along with transcutaneous electrical nerve stimulation in patients with malignant pleural effusion with intercostal drainage tube: a randomized controlled trial - Gunjal, Sambhaji B.; Jain, Vandana (International Journal of Research in Medical Sciences, 2023)
Background: Malignant pleural effusion (MPE) is one of the most common causes of an exudative pleural effusion. It is the most common cause of a unilateral massive pleural effusion. Most MPE s are secondary to metastases to the pleura, most often from lung or breast cancer. Medical management includes aspiration of fluid with the insertion of a chest tube, which may be necessary to relieve dyspnea. Hypoventilation does occur in certain areas of the lungs because of pain and muscle guarding after intercostal drainage tube (ICD) tube placements in pleural effusion. Therefore, it is important to emphasize pain management and expansion of affected areas of the lungs and chest wall. SMI is the basic maneuver of incentive spirometry and is mainly given to prevent atelectasis and lung collapse in postoperative patients. TENS is a method of producing an electro-analgesic effect and is effective in providing post-operative pain control. Methods: The study design of the study was a randomized controlled trial. A total of 44 participants with a diagnosis of MPE with an intercostal drainage tube were included in this study. The study duration was 5 years with an intervention period of 2 weeks and the outcome measures were pulmonary functions and intercostal pain severity using the NRS Scale. Results: There was a significant improvement in pulmonary functions in the control group and a highly significant improvement in pulmonary functions in the experimental group after 2 weeks of interventions and pain severity (NRS) was significantly reduced in the experimental group only (p<0.001) Conclusions: This study concluded that sustained maximal inspiration (SMI) along with TENS significantly improves pulmonary functions and reduces pain at the site of ICD in patients with MPE.